Acetylation of Response Regulator Protein MtrA in M. tuberculosis Regulates Its Repressor Activity - Singh, Krishna Kumar; Athira, P. J.; Bhardwaj, Neerupma; Singh, Devendra Pratap; Watson, Uchenna; Saini, Deepak Kumar (Frontiers in Microbiology, 2021)
MtrA is an essential response regulator (RR) protein in M. tuberculosis, whose activity is modulated after phosphorylation from its sensor kinase MtrB. Interestingly many regulatory effects of MtrA have been reported to be independent of its phosphorylation, thereby suggesting alternate mechanisms of regulation of the MtrAB two-component system in M. tuberculosis. Here we show that RR MtrA undergoes non-enzymatic acetylation through acetyl phosphate, modulating its activities independent of its phosphorylation status. Acetylated MtrA shows increased phosphorylation and enhanced interaction with SK MtrB assessed by phosphotransfer assays and FRET analysis. We also observed that acetylated MtrA loses its DNA-binding ability on gene targets, otherwise enhanced by phosphorylation. More interestingly, acetylation is the dominant post-translational modification, overriding the effect of phosphorylation . Evaluation of the impact of MtrA and its lysine mutants overexpression on the growth of H37Ra bacteria under different conditions along with the infection studies on alveolar epithelial cells further strengthens the importance of acetylated MtrA protein in regulating the growth of M. tuberculosis. Overall, we show that both acetylation and phosphorylation regulate the activities of RR MtrA on different target genomic regions. We propose here that while phosphorylation-dependent binding of MtrA drives its repressor activity on oriC and rpf, acetylation of MtrA turns this off and facilitate division in mycobacteria. Our findings thus reveal a more complex regulatory role of RR proteins where multiple post-translational modifications regulate the activities at the levels of interaction with SK and the target gene expression.